Disease associated balanced chromosome rearrangements: a resource for large scale genotype-phenotype delineation in man. Issue 11 (1st November 2000) - Bugge, Merete; Bruun-Petersen, Gert; Brøndum-Nielsen, Karen; Friedrich, Ursula; Hansen, Jan; Jensen, Grethe; Jensen, Peter K A; Kristoffersson, Ulf; Lundsteen, Claes; Niebuhr, Erik; Rasmussen, Kim R; Rasmussen, Kirsten; et al.
Abstract : Disease associated balanced chromosomal rearrangements (DBCRs), which truncate, delete, or otherwise inactivate specific genes, have been instrumental for positional cloning of many disease genes. A network of cytogenetic laboratories, Mendelian Cytogenetics Network (MCN), has been established to facilitate the identification and mapping of DBCRs. To get an estimate of the potential of this approach, we surveyed all cytogenetic archives in Denmark and southern Sweden, with a population of ∼6.6 million. The nine laboratories have performed 71 739 postnatal cytogenetic tests. Excluding Robertsonian translocations and chromosome 9 inversions, we identified 216 DBCRs (∼0.3%), including a minimum estimate of 114 de novo reciprocal translocations (0.16%) and eight de novo inversions (0.01%). Altogether, this is six times more frequent than in the general population, suggesting a causal relationship with the traits involved in most of these cases. Of the identified cases, only 25 (12%) have been published, including 12 cases with known syndromes and 13 cases with unspecified mental retardation/congenital malformations. The remaining DBCRs were associated with a plethora of traits including mental retardation, dysmorphic features, major congenital malformations, autism, and male and female infertility. Several of the unpublished DBCRs defined candidate breakpoints for nail-patella, Prader-Willi, and Schmidt syndromes, ataxia, and ulna aplasia. The implication of the survey is apparent when compared with MCN; altogether, the 292 participating laboratories have performed >2.5 million postnatal analyses, with an estimated ∼7500 DBCRs stored in their archives, of which more than half might be causative mutations. In addition, an estimated 450-500 novel cases should be detected each year. Our data illustrate that DBCRs and MCN are resources for large scale establishment of phenotype-genotype relationships in man.